A Review of Continuous Manufacturing in Pharmaceutical Process Monitoring - Pradip Iramdhan Aliyansah (Journal of Science and Technology Research for Pharmacy, 2022)
This review explores continuous manufacturing (CM) process monitoring in the pharmaceutical industry and its advantages over batch processes. The case study focuses on CM production of solid dosage forms, using a water-based wet granulation method. The research proposes a monitoring strategy through in-process control (IPC), process analytical technology (PAT), and critical process parameters (CPPs). The study demonstrates that the CM process is robust and provides satisfying results, with critical quality attributes (CQAs) meeting target specifications. The role of IPC and PAT in ensuring product quality is highlighted, with IPC used to monitor and adjust processing operations, while PAT enables real-time monitoring of drug content. The advantages of CM include improved product quality, agility in drug development, elimination of scaling-up challenges, and reduced environmental exposure. However, implementing CM requires a systematic approach and significant capital investment. The review concludes that CM offers benefits despite the challenges and presents a promising approach to modernizing pharmaceutical manufacturing.